Influence of plastic deformation on the change of electrical and mechanical properties oxygen-free (OF) copper and copper alloy wires - T. Knych; A. Mamala; A. Kawecki; B. Smyrak; K. Korzen; E. Sieja-Smaga (Metalurgija, 2022)
This article is devoted to the comparison of changes in mechanical and electrical properties due to the applied deformation of copper and copper alloy rods. Bars from four different production technologies were deformed in the drawing process, including oxygen-free (OF) copper, electrolytic copper ETP, copper from cable granulate and silver copper with a high silver content up to 15 wt. % obtained in laboratory technology. The article presents the chemical purity, physical and electrical properties of rods before deformation. The summary of the research on the selected materials are changes in mechanical properties and electrical conductivity as a function of deformation up to 3,5 on a logarithmic scale and the coefficient of electromechanical efficiency WEM.